Enforcement of the Criminal Act of Trafficking in Women - Ridho, Rendy Arsy; Pratiwi, Siswantari; Mardani (JILPR Journal Indonesia Law and Policy Review, 2024)
Cases of human trafficking in Indonesia are currently very widespread. Apart from being used as sexual exploitation in Indonesia, the most common cases of human trafficking in Indonesia are cases of prostitution where people are trafficked in providing sexual services that can be ordered online. This of course creates unrest among the wider community. There are so many cases of human trafficking in cyberspace that occur and of course many of these cases have not been revealed because apart from the performance of law enforcement officers, it is also due to the inadequate legal regulations and criminal sanctions in dealing with human trafficking cases in cyberspace. cyberspace. The provisions in Law Number 19 of 2016 concerning Electronic Information and Transactions and Law Number 21 of 2007 concerning the Eradication of the Criminal Act of Human Trafficking do not regulate in detail all aspects regarding sanctions, elements and other matters regarding human trafficking. in cyberspace, both from Law Number 19 of 2016 concerning Electronic Information and Transactions and Law Number 21 of 2007 concerning the Eradication of the Crime of Human Trafficking and it is felt necessary to revise or further refine existing regulations so that later criminal sanctions can be imposed. These regulations can be used as a countermeasure. In this research, researchers try to examine the case of Decision Number 841/Pid.Sus/2019/PN Mdn and Decision Number: 180/Pid.Sus/2016/PN Psp, Decision Number 841 / Pid.Sus / 2019 / PN Mdn and in the research This time, researchers tried to examine the case of Decision Number 841/Pid.Sus/2019/PN Mdn and Decision Number: 180/Pid.Sus/2016/PN Psp, Decision Number 841 / Pid.Sus / 2019 / PN Mdn with the defendant named Mujiono alias Edak is an entrepreneur whose address is Hamlet III, Liberia Village, Kec. Mengkudu Bay District. Serdang Bedagai. The public prosecutor has submitted the defendant to trial on the charge of declaring that the defendant MUJIONO als EDAK has been legally and convincingly proven to have committed a criminal act ", who carried out recruitment, for the purpose of exploiting said person in the territory of the Republic of Indonesia" as regulated and punishable by crime in Article 2 of the Law Number 21 of 2007 concerning Eradication of the Crime of Human Trafficking.